Environmental Ethics in the Quran: A Study of Semantic Analysis and Interpretation of the Term "Khalifah" - Ihsan, Nur Hadi; Syahrinal, Syahrinal; Shalahudin, Henri (Proceedings of International Conference on Muslim Society and Thought, 2024)
The term ?khalifah? is often equated with leadership, referring to a perspective that interprets it as a derivation of the term ?imamah.? While not entirely incorrect, many view it as a definitive meaning. However, referring to the Quran, ?khalifah? holds a broader and more universal significance. The limited understanding of ?khalifah? as merely a leader seems to have narrowed its original meaning. Therefore, this research aims to delineate the concept of ?khalifah? through semantic analysis and interpretations from authoritative Quranic commentators. In this research method, we employ literature review with a qualitative approach, and data collection is conducted through documentary techniques to gather data from various verses in the Quran as well as explanations from Quranic scholars in classical and contemporary tafsir literature. The collected data is then analyzed using content analysis method. The results of this research indicate that the term ?khalifah? in the Quran signifies a trust and responsibility of humans on Earth to prosper it and preserve its flora and fauna. Verses related to ?khalifah? depict that it plays a crucial role in maintaining the balance of nature. This research has significant implications in the context of environmental conservation. Additionally, these findings provide a deeper insight into the importance of building a harmonious relationship between humans and nature, both being creations of Allah.